Aspek Onthologis Bahasa dan Filsafat - I Wayan Mawa (WACANA : MAJALAH ILMIAH TENTANG BAHASA, SASTRA DAN PEMBELAJARANNYA, 2019)
Lingustics and philosophy are two different disciplines. Although they are two discipline they have very close relationship for instance in case at systematic grammatical analysis. Beside that, other linguistics on philospy both of them are the result at thinking process, linguistics could help us to understand philosophy start from the thinking process of an abstact concept and also linguistics and philosophy have concepts and principles about universal dialing with and culture.